2014
DOI: 10.1063/1.4874850
|View full text |Cite
|
Sign up to set email alerts
|

Communication: Helium nanodroplet isolation and rovibrational spectroscopy of hydroxymethylene

Abstract: Single and double resonance spectroscopy of methanol embedded in superfluid helium nanodroplets

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 36 publications
4
8
0
Order By: Relevance
“…More recently, HCOH and its d 1 -isotopologue (HCOD) were isolated in He droplets at 0.4 K. 35 Rotationally resolved spectra of these species isolated in the weakly perturbing He environment enabled an assignment of several bands in the X-H(D) stretching region to the trans-HCOH(D) isomers, in agreement with the predictions of anharmonic frequency computations and consistent with the assignments of the Ar matrix spectra.…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…More recently, HCOH and its d 1 -isotopologue (HCOD) were isolated in He droplets at 0.4 K. 35 Rotationally resolved spectra of these species isolated in the weakly perturbing He environment enabled an assignment of several bands in the X-H(D) stretching region to the trans-HCOH(D) isomers, in agreement with the predictions of anharmonic frequency computations and consistent with the assignments of the Ar matrix spectra.…”
Section: Introductionsupporting
confidence: 63%
“…45,49,50 The droplets pass into a differentially pumped "pickup" chamber, where gas-phase molecules are captured, solvated, and cooled to ≈0.4 K. 51 A low-pressure, effusive pyrolysis source located in the pickup chamber produces gas-phase carbenes by thermal decomposition of organic precursor molecules. 35 Gas-phase HOCOH was generated via pyrolysis of oxalic acid (C 2 H 2 O 4 ), analogous to the procedure reported by Schreiner and co-workers. 36 The pyrolysis region consisted of a 15 cm long quartz tube with an outer diameter of 0.6 cm, which is oriented perpendicular to the droplet beam.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…We now expect the OH stretch bands of matrix-isolated hydroxycarbene systems to be red-shifted from the He droplet band origins by 30 cm -1 . Indeed, similarband origin differences were observed for both hydroxymethylene and dihydroxycarbene [20,30]. Apparently, the solid Ar matrix environment exerts a significant perturbation to the OH oscillators in these systems.…”
Section: Oh-survey Spectrumsupporting
confidence: 52%
“…The IR spectra reported here represent the laser-induced depletion signal in a single mass channel. Based upon previous work on HC OH and HOC OH in He droplets [20,30],we found that mass 29 u, corresponding to (HCO + ), was a major fragmentation product of the electronimpact ionization process for the hydroxycarbene doped He droplets. Moreover, significant laser-induced depletion signal was observed in the 29 u mass channel when the laser was tuned into resonance with the OH or CH stretching bands of these species.…”
Section: Oh-survey Spectrummentioning
confidence: 77%
See 1 more Smart Citation